Three-dimensional mono-6-thio-β-cyclodextrin covalently functionalized gold nanoparticle/single-wall carbon nanotube hybrids for highly sensitive and selective electrochemical determination of methyl parathion. (20th January 2015) - Fu, Xu-Cheng; Zhang, Jian; Tao, Yuan-Yuan; Wu, Ju; Xie, Cheng-Gen; Kong, Ling-Tao
Abstract: This work described the fabrication of a gold nanoparticles/single-walled carbon nanotubes/glassy carbon electrode containing mono-6-thio-β-cyclodextrin (SH-β-CD) self-assembled monolayer (SH-β-CD/AuNPs/SWCNTs/GCE) and its application for electrochemical determination of methyl parathion (MP) pesticide in solution using square wave anodic stripping voltammetry (SWV) method. The SH-β-CD/AuNPs/SWCNTs nanohybrids had a three-dimensional porous nanostructure with large active surface area, and the SH-β-CD monolayer on AuNPs/SWCNTs surface could greatly enhance the sensitivity and selectivity in detecting MP pesticides. The SWV response of the MP on the SH-β-CD/AuNPs/SWCNTs/GCE was ca. 3.9 and 5.1 times that of MP on the SH-β-CD/AuNPs/GCE and AuNPs/SWCNTs/GCE, respectively. The sensor demonstrated a wide linear response range from 2.0–80.0 nM, with a lower detection limit of 0.1 nM (S/N = 3) using 180 s of preconcentration time. The interference experiments showed that other aromatic insecticide, such as, chlorpyrifos, 2, 4-dDichlorophenoxy acetic acid, methamidophos, triazophos, parathion had little influence on the MP signal. The proposed sensor was further employed for detection of MP in the real environmental water sample.